Proteases and Cancer Methods and Protocols - Bugge, Thomas H.; Antalis, Toni M.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2009)
Proteases decisively contribute to cancer development and promotion by regulating the activities of growth factors/cytokines and signaling receptors, as well as the composition of the extracellular matrix, thereby suppressing cell death pathways and activating cell survival pathways. In Proteases and Cancer: Methods and Protocols, expert researchers bring together a wide range of current, complimentary techniques that have been developed for the specific detection and analysis of proteases and their activities in cancer biology. The volume covers vital topics including the application of proteomics technologies for the detection of protease expression in tumors, imaging proteases by activity profiling, proteomics technologies for the identification of biological substrates, detection of cell surface proteolysis, imaging of protease activity, the use of transgenic mice to determine protease function in tumor initiation and progression, and the development of anti-protease therapies for cancer. Written in the highly successful Methods in Molecular Biology$1!" (Bseries format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easy to use, Proteases and Cancer: Methods and Protocols is an ideal guide for scientists who wish to pursue the study of this important branch of cancer research and the development of unique innovative technologies to aid in that study.s
Delineating Protease Functions During ?Cancer Development -- Proteolytic Systems: Constructing Degradomes -- Microarrays for Protease Detection in Tissues and Cells -- Positional Scanning Synthetic Combinatorial Libraries for Substrate Profiling -- Mixture-Based Peptide Libraries for Identifying Protease Cleavage Motifs -- High Throughput Substrate Phage Display for Protease Profiling -- Imaging Specific Cell Surface Protease Activity in Living Cells Using Reengineered Bacterial Cytotoxins -- Cell-Based Identification of Natural Substrates and Cleavage Sites for Extracellular Proteases by SILAC Proteomics -- Optical Proteolytic Beacons for In Vivo Detection of Matrix Metalloproteinase Activity -- Dissecting the Urokinase Activation Pathway Using Urokinase-Activated Anthrax Toxin -- On-Demand Cleavable Linkers for Radioimmunotherapy.
Keywords: Medicine; Cancer research; Enzymology; Biomedicine; Cancer Research; Enzymology; Electronic books